1987
DOI: 10.1002/zoo.1430060303
|View full text |Cite
|
Sign up to set email alerts
|

Urinary steroid evaluations to monitor ovarian function in exotic ungulates: IV. Estrogen metabolism in the okapi (Okapia johnstoni)

Abstract: In this investigation, an attempt was made to identify the major urinary estrogen metabolites in the okapi by radioisotope infusion and by chromatographic separation procedures. The results suggest that the urinary estrogens are excreted in concentrations below the limit of sensitivity of conventional assay systems. In addition, a variety of contaminants with estrogenic immunoreactivity are present in okapi urine that are not necessarily correlated with follicular activity. A great proportion of circulating es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…Although fecal monitoring has been used in other avian species to measure daily changes in sex steroid production [Bishop and Hall, 1991;Yamaguchi and Ishii, 1991;Cockrem and Rounce, 1994;Lee et al, 1995], the present data are the first to demonstrate that daily fecal/urine measurements reflect primarily the excretion products of estradiol and testosterone produced during the previous 24 hr. These results are unlike mammalian studies in which radiolabeled steroid excretion has been relatively slow and overall recovery has been low [Shille et al, 1984;Loskutoff et al, 1987;Ziegler et al, 1989;Hindle and Hodges, 1990;Czekala et al, 1992;Shideler et al, 1993]. The present report reveals a recovery of 75% of each radiolabeled steroid administered within 24 hr after radiolabel injection.…”
Section: Discussioncontrasting
confidence: 83%
“…Although fecal monitoring has been used in other avian species to measure daily changes in sex steroid production [Bishop and Hall, 1991;Yamaguchi and Ishii, 1991;Cockrem and Rounce, 1994;Lee et al, 1995], the present data are the first to demonstrate that daily fecal/urine measurements reflect primarily the excretion products of estradiol and testosterone produced during the previous 24 hr. These results are unlike mammalian studies in which radiolabeled steroid excretion has been relatively slow and overall recovery has been low [Shille et al, 1984;Loskutoff et al, 1987;Ziegler et al, 1989;Hindle and Hodges, 1990;Czekala et al, 1992;Shideler et al, 1993]. The present report reveals a recovery of 75% of each radiolabeled steroid administered within 24 hr after radiolabel injection.…”
Section: Discussioncontrasting
confidence: 83%
“…Pregnancy in okapi could not be diagnosed using our assay of fecal iE 2 and iE 1 . It has been reported that a variety of contaminants with estrogenic immunoreactivity are present in okapi urine [10]. When assaying fecal estrogens, a pretreatment such as purification of fecal steroid extracts may be required.…”
Section: Discussionmentioning
confidence: 99%
“…However, the day of their peak could not be identified since fecal samples were not collected on the day of parturition and the 2nd and 3rd days postpartum. Given the report that tritiated E 2 infused via the jugular vein was detected in feces at 72 h post-injection [10], circulating estrogens probably take 3 days to be excreted in feces. It seems that the circulating levels of estrogens reached a peak within the period from 3 days prepartum to the day of parturition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations